New Onset Insomnia in a Pediatric Patient: A Case of Anti-NMDA Receptor Encephalitis - Tamar N. Goldberg; Michael F. Cellucci (Case Reports in Pediatrics)
Anti-NMDAR encephalitis is becoming more widely recognized as a cause of encephalopathy in both adults and children. Certain clinical features such as mood lability, movement disorders, speech dysfunction, seizures, and autonomic instability in a pediatric patient should prompt immediate concern and evaluation for autoimmune encephalitis among providers. We present the case of a pediatric patient with anti-NMDAR encephalitis in which the symptom prompting medical evaluation was insomnia. Insomnia has not previously been emphasized in the literature as a presenting feature of this disease in children and has a broad differential. Recognition of the symptoms of anti-NMDAR encephalitis and its variable presentation are key to early diagnosis and prompt initiation of treatment which may help to improve outcomes.